LncRNA Chaer Prevents Cardiomyocyte Apoptosis From Acute Myocardial Infarction Through AMPK Activation - He, Zhiyu; Zeng, Xiaojun; Zhou, Deke; Liu, Peiying; Han, Dunzheng; Xu, Lingling; Bu, Tong; Wang, Jinping; Ke, Mengmeng; Pan, Xiudi; Du, Yipeng; Xue, Hao; et al. (Frontiers in Pharmacology, 2021)
Long non-coding RNA (lncRNA) is widely reported to be involved in cardiac (patho)physiology. Acute myocardial infarction, in which cardiomyocyte apoptosis plays an important role, is a life-threatening disease. Here, we report the lncRNA Chaer that is anti-apoptotic in cardiomyocytes during Acute myocardial infarction. Importantly, lncRNA Chaer is significantly downregulated in both oxygen-glucose deprivation (oxygen-glucose deprivation)-treated cardiomyocytes in vitro and AMI heart. In vitro, overexpression of lncRNA Chaer with adeno virus reduces cardiomyocyte apoptosis induced by OGD-treated while silencing of lncRNA Chaer increases cardiomyocyte apoptosis instead. In vivo, forced expression of lncRNA Chaer with AAV9 attenuates cardiac apoptosis, reduces infarction area and improves mice heart function in AMI. Interestingly, overexpression of lncRNA Chaer promotes the phosphorylation of AMPK, and AMPK inhibitor Compound C reverses the overexpression of lncRNA Chaer effect of reducing cardiomyocyte apoptosis under OGD-treatment. In summary, we identify the novel ability of lncRNA Chaer in regulating cardiomyocyte apoptosis by promoting phosphorylation of AMPK in AMI.